THE EFFECT OF MODIFIED HIMALAYAN SALT ON REDUCING BLOOD PRESSURE IN HYPERTENSION PATIENTS AT THE DELI TUA COMMUNITY HEALTH CENTER IN 2024 - Silalahi, Rini Debora; Purba, Rentawati (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2025)
Abstract One of the main causes of death and disability on a global scale, hypertension affects a large percentage of the population. Modifying one's eating habits and level of physical activity are two key components of a hypertension management plan. As a serious and widely-present health problem, hypertension is frequently encountered in primary healthcare institutions in Indonesia. Despite the availability of effective medications at healthcare facilities, the public's lack of information about hypertension management and control contributes to the high frequency of the disease in Indonesia. Both pharmaceutical and non-pharmacological methods exist for the management of hypertension. Medication is the cornerstone of pharmacological treatment, which aims to reduce and stabilise blood pressure. Medication must be taken consistently in order for this treatment to work. The use of medicinal drugs is not part of non-pharmacological therapy. Complementary therapy is one form of treatment that does not involve pharmaceuticals. The primary objective of this research is to determine whether hypertension individuals' blood pressure can be reduced by adjusting their intake of Himalayan salt. This study employed a one-group pretest-posttest design, which is typical of quasi-experimental research. The paired sample test was used to analyse the data. The complete sampling method was used to get 21 samples. The data was collected by use of observation sheets. The bivariate study conducted at the Deli Tua Public Health Centre in 2024 found a p-value of 0.000 < 0.05, suggesting that changing the consumption of Himalayan salt had an influence on reducing blood pressure in hypertensive individuals. Keywords: Hypertension, Himalayan Salt Consumption, Blood Pressure.